2021
DOI: 10.1128/spectrum.00181-21
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Efficacy of Gentamicin Alone and in Combination with Ceftriaxone, Ertapenem, and Azithromycin against Multidrug-Resistant Neisseria gonorrhoeae

Abstract: Antimicrobial-resistant Neisseria gonorrhoeae is a major global public health concern. New treatment options are urgently needed to successfully treat multidrug-resistant (MDR) Neisseria gonorrhoeae infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…54 Over time, N. gonorrhoeae acquired resistance to these antimicrobials due to cumulative mutations in the PBPs and multidrug MtrCDE efflux pumps. 55 In 2018, an extreme drug-resistant gonococcal strain was reported in the UK, requiring 6,40 the search for a newer set of targets and inhibitors. The NgA, which remained highly conserved within the N. gonorrhoeae pathogen sequence database, appears to be serving the purpose (Figures 1B and 5A).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…54 Over time, N. gonorrhoeae acquired resistance to these antimicrobials due to cumulative mutations in the PBPs and multidrug MtrCDE efflux pumps. 55 In 2018, an extreme drug-resistant gonococcal strain was reported in the UK, requiring 6,40 the search for a newer set of targets and inhibitors. The NgA, which remained highly conserved within the N. gonorrhoeae pathogen sequence database, appears to be serving the purpose (Figures 1B and 5A).…”
Section: Discussionmentioning
confidence: 99%
“…N. gonorrhoeae was initially cultured on Thayer Martin agar (HiMedia Laboratories), a selective media supplemented with vancomycin, colistin, nystatin, and trimethoprim for screening and maintaining pure N. gonorrhoeae colonies. For further experiments, N. gonorrhoeae was preinoculated in GC chocolate agar (HiMedia Laboratories) supplemented with 2% haemoglobin and vitamin growth supplement (HiMedia Laboratories) at 37°C in a humid candle jar overnight 40 . The inhibitory concentration (IC 50 ) for N2, N8, and N9 was studied by broth microdilution method using 3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide (MTT) and resazurin‐based cell viability assay (REMA) described earlier 21,41,42 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By the agar dilution method, we found that 36.60% of the isolates were fully susceptible to gentamicin, while 61.30% of the strains showed intermediate susceptibility. In two other studies from China on N. gonorrhoeae susceptibility to gentamicin, moderate susceptibility rates of 97.8% [ 25 ] and 91.6% [ 21 ] were also reported. The possible reason was that these two studies were both from eastern provinces of China, while the isolates of our study were from the eastern, northern and western regions of China.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria for azithromycin and ceftriaxone susceptibility and resistance were interpreted based on the Clinical and Laboratory standards Institute (CLSI) M100-S29 breakpoints [ 20 ]. According to previous studies and interpretation criteria, the breakpoint for gentamicin MIC was set to be ≤4 mg/L as fully susceptible, 8 to 16 mg/L as intermediately susceptible, and ≥32 mg/L as resistant [ 14 , 21 ].…”
Section: Methodsmentioning
confidence: 99%